2020
DOI: 10.4103/tjo.tjo_18_20
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the pathogenesis of thyroid-associated ophthalmopathy and new drug development

Abstract: Thyroid-associated ophthalmopathy (TAO) is the most common extrathyroidal manifestation of toxic diffuse goiter (Graves' disease), also known as Graves' ophthalmopathy/orbitopathy. As an organ-specific autoimmune disease, the pathogenesis of TAO is still unclear. In recent years, great progress has been made in revealing the mechanism of TAO. Various biological and immunosuppressive agents have emerged in an endless stream, showing encouraging results. Strengthening the basic research, establishing ideal anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 80 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The underlying reason determines the origin of the higher orbital content. Graves ophthalmopathy causes extraocular muscle growth and orbital adipose tissue expansion due to aberrant hyaluronic acid buildup and edema collection into the retro-orbital space (Huang et al, 2020). T cells detect thyroid-orbit antigens and infiltrate the orbit and extraocular muscle perimysium.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying reason determines the origin of the higher orbital content. Graves ophthalmopathy causes extraocular muscle growth and orbital adipose tissue expansion due to aberrant hyaluronic acid buildup and edema collection into the retro-orbital space (Huang et al, 2020). T cells detect thyroid-orbit antigens and infiltrate the orbit and extraocular muscle perimysium.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggested that pathological angiogenesis and damage repair are strictly regulated by m6A modification subsequent to corneal chemical burns. Graves' Ophthalmopathy GO, also called thyroid-associated ophthalmopathy, is an orbital disorder of autoimmune pathology that predominantly attacks extraocular muscles (EOMs) and is the most common extrathyroidal symptom of Graves' disease [63] . The clinical features of GO are complicated, including double vision, exophthalmos, eyelid retraction, diplopia, restrictive strabismus, exposure keratopathy, and optic neuropathy [64][65] .…”
Section: M6a Modification In Ocular Surface Diseasesmentioning
confidence: 99%
“…The pathological hallmarks of TAO include orbital inflammatory infiltration, over-production of hydrophilic glycosaminoglycans, de novo adipogenesis, and tissue fibrosis. In the presence of genetic, autoimmune and environmental factors, autoimmune T cells, B cells, and OF are activated by unbalanced immune tolerance, resulting in a series of inflammatory responses, including cellular and humoral immunity [ 21 , 22 ]. The overproduction of hydrophilic glycosaminoglycans, especially hyaluronan (HA), leads to orbital tissue edema, which, together with de novo adipogenesis, causes orbital tissue expansion [ 6 , 18 , 23 , 24 ].…”
Section: Pathophysiology Of Taomentioning
confidence: 99%